2018
DOI: 10.12693/aphyspola.134.1180
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Corresponding Magnetic Properties of Sputtered Ni/Al Multilayer Films: Effect of Ni Layer Thickness

Abstract: A series of Ni/Al multilayers with different thicknesses of Ni layers was produced by a sputtering technique. The deposition parameters of optimum magnetic properties for write heads were detected by scanning the magnetic layer thickness from 0 to 70 nm. The optimum magnetic properties were decided by obtaining the saturation magnetization, Ms, coercivity, Hc and Ms/Hc ratios from the hysteresis loops. A face centered cubic (fcc) structure was established for all films. Transition surface morphology; i.e., a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The decrease in the H C values of the films can be associated with the decrease in the amount of Al in the film content and, simpler and uniform surface morphologies with the increase in the Ni deposition rate. There are no studies about the magnetic properties of Ni/Al multilayer thin films except for our previous two investigations [16,17]. The saturation magnetisation and coercivity values under study are found to be consistent with these studies.…”
Section: Magnetic Properties Of the Filmssupporting
confidence: 76%
See 3 more Smart Citations
“…The decrease in the H C values of the films can be associated with the decrease in the amount of Al in the film content and, simpler and uniform surface morphologies with the increase in the Ni deposition rate. There are no studies about the magnetic properties of Ni/Al multilayer thin films except for our previous two investigations [16,17]. The saturation magnetisation and coercivity values under study are found to be consistent with these studies.…”
Section: Magnetic Properties Of the Filmssupporting
confidence: 76%
“…According to the results, the Ni contents in the films increased with the increase in Ni deposition rate. The contents of the films show the same trend as the content ratios obtained in the study [16], in which the effects of different layer thicknesses of Ni layers for Ni/Al multilayer films were investigated. As seen in figure 3, with the increase in Ni deposition rate, the peak of the (111) plane of the face-centred cubic (fcc) Al, which is formed at Bragg angle of ∼38.4°.…”
Section: Contents Of the Filmssupporting
confidence: 68%
See 2 more Smart Citations
“…This observation is crucial to understand how the morphology and magnetic properties evolve with layer thickness and preparation conditions. These studies focused in particular on systems based on SmCo, SmFe, FePt, CoFe(Cu), CoFeNi, Fe, or Co. [ 10–20,20–22 ] Films based on the ZrCo alloy represent a significant advance in the field of magnetic materials, due to their application potential in cutting‐edge areas. [ 23–29 ] These films provide a unique platform to study the interactions between different magnetic phases, combining hard and soft magnetic layers.…”
Section: Introductionmentioning
confidence: 99%